Improving linkages between policy and implementation across Africa - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Dr. Shadrack Moephuli, CEO at the Agricultural Research Council in South Africa speaks about the work done at his organization to improve linkages between policy and implementation across Africa. The Forum for Agricultural Research in Africa (FARA) in collaboration with the Government of Ghana convened the 6th Africa Agriculture Science Week from July 15-19 in Accra, a continental gathering of all stakeholders involved in African agriculture. Learn more: https://ccafs.cgiar.org/blogs/aasw6 http://www.fara-africa.org/scienceweek/